The Impact of Pay and Perquipment on Worker Performance at UD Nilam Sari Nganjuk - Aini, Nurul Nur; Rukmini, Meme; Yap, Nonni (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2024)
This study examines the impact of pay and perquisites on worker performance at UD. Nilam Sari Nganjuk. The research aims to identify the extent to which financial compensation and non-financial benefits influence employees' productivity and job satisfaction. Using a quantitative research design, data were collected through surveys distributed to 50 employees of the company. The findings indicate a significant positive relationship between pay and worker performance, suggesting that competitive salaries motivate employees to perform better. Similarly, the provision of perquisites, such as bonuses, allowances, and welfare benefits, was found to enhance employee satisfaction and overall productivity. The study concludes that optimizing both pay and perquisites can serve as a strategic tool to boost worker performance and organizational effectiveness. Recommendations for the company include periodic salary reviews and the introduction of innovative employee benefits to sustain motivation and improve performance. Keywords : Worker Performance, Financial Compensation, Non-Financial Benefits, Job Satisfaction, Productivity